Estrutura das Cipselas de Richterago Kuntze e Moquiniastrum (Cabrera) G. Sancho (Gochnatieae - Asteraceae) - Cantuario, Evelise Vieira (2022)
Moquiniastrum and Richterago are both part of the Gochnatieae tribe, which is one of the earliest diverging lineages in Asteraceae and is commonly referred to as one of the basal tribes. This study described the structure of the cypselae of nineteen species of Moquiniastrum and sixteen species of Richterago. The cypselae used in this study were obtained from herbaria specimens. A pattern was found in the anatomy of the studied species, as described below: the exocarp is uniseriate with an ornamented cuticle. The mesocarp is aerenchymatous with a variable number of layers. The vascular bundle is collateral, and the innermost layers, such as the inner mesocarp and endocarp, are consumed. In the basal region, the carpopodium is vascularized with a uniseriate exocarp whose cells are juxtaposed and lignified. No characteristics of taxonomic value were found in this region. The pappus is vascularized, and its bristles cells are lignified. The exotesta of Moquiniastrum has lignin thickening on the anticlinal walls and internal periclinal wall, which confers a U-shaped appearance in the cross section. On the other hand, Richterago presented a thickening of the anticlinal and periclinal walls that are completely lignified. The rapheal bundle extends to the chalaza. The results obtained add characteristics that contribute to the understanding of the studied genera and the Gochnatieae tribe.